Effect of Salinity on Evaporation and the Water Cycle - Jude Iloabuchi Obianyo (Ital Publication, 2019)
This study is on the effect of salinity on evaporation from water bodies and its probable influence on the water cycle. Five different salts were used in this study. Different concentrations of Magnesium Sulphate, Sodium Hydroxide, Sodium Chloride, Ammonium Chloride, and Potassium Nitrate solutions in the neighbourhood of 0.04, 0.08, 0.12, 0.16, 0.20, and 0.24 g/cm3 were prepared by dissolving 20, 40, 60, 80, 100, and 120 g weights of these salts in 500 cm3 of distilled water. The first evaporation could contain only 500 cm3 of distilled water and served as the control experiment. The solutions were introduced into evaporation cans, each with a capacity of 700 cm3, stored at room temperature, and evaporation was allowed to take place. Evaporation from the cans was measured at 24 hour intervals for a period of 14 days. Results showed that in all salts, as salinity increases, evaporation is reduced. On the 10th day, evaporation retardation factors for Magnesium Sulphate, Sodium Hydroxide, Sodium Chloride, Ammonium Chloride, and Potassium Nitrate were found to be 0.800, 0.490, 0.712, 0.820, and 0.822, respectively. Ratios of evaporation retardation factors were 1:1.6327 for Sodium Hydroxide: Magnesium Sulphate; 1:1.4531 for Sodium Hydroxide: Sodium Chloride; 1:1.6735 for Sodium Hydroxide: Magnesium Sulphate; 1:1.4531 for Sodium Hydroxide: Sodium Chloride; 1:1.6327 for Sodium Hydroxide: Ammonium Chloride and 1:1.6776 for Sodium Hydroxide: Potassium Nitrate solutions. The highest evaporation took place in Potassium Nitrate solution at an ultimate concentration of 0.24 g/cm3. This was followed by Ammonium Chloride, Magnesium Sulphate, Sodium Chloride and Sodium Hydroxide. This salinity effect will impact on the outflow parameter in the water cycle with a consequent reduction in evaporation, which reduces precipitation. Hence, the formation of rain in the cloud will be inhibited and ultimately lead to climate change.